Analisis Hukum Terhadap Penggunaan dan Pembuatan Akta Notaris Secara Elektronik Dengan Menggunakan Artifisial Intelegensi (AI) - Frita Apriliana Yudha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Several countries have implemented electronic notarial deeds in their national legal systems, mainly to ensure the authenticity of electronic information. The authentic deed rules in the UUJN and Civil Code show that the use of notarial deeds and the creation of authentic deeds are difficult to implement due to the absence of procedural changes. The definition of an authentic deed is included in both UUJN and UU ITE. The research findings show that the creation of electronic deeds using artificial intelligence (AI) has become a legal basis. For example, Article 15(3) of the UUJN and Article 17 of the UUPT cover electronic registration of trust deeds, electronic registration with notaries, amendments to the articles of association of legal entities, and so on. Obstacles in the implementation of electronic deeds are influenced by many factors, such as legal substance, legal structure, and legal culture.